MicroRNA-155 modulates methotrexate-induced spatial memory impairment by disruption of the blood-brain barrier integrity - Yu-Chieh Chen; Li-Tung Huang; Hong-Ren Yu; Jiunn-Ming Sheen (Brain Research Bulletin)
Aim: Methotrexate (MTX) is a commonly used chemotherapy drug, yet its late neurotoxic side effects are gaining attention. The aim of the study was to evaluate the role of miR-155 in the pathogenesis of MTX-induced cognitive impairment, mainly focused on the interplay of blood-brain barrier (BBB) integrity and MTX toxicity. Main methods: We use young rat model mimicking children leukemia treatment protocol, focusing on the systemic MTX effect on the central nervous system by intraperitoneal (IP) MTX injection. The cognitive function was evaluated by Morris Water Maze test and the BBB integrity was accessed by cortex permeability test. Tight junction proteins expression were also examined. Finally, we tested whether anti-miR155 pretreatment can reversed the MTX effect. Key findings: We found increased plasma miR-155 expression at 24 hr after IP MTX treatment. Besides, IP MTX resulted in impaired learning acquisition, which can be reversed by anti-miR155 treatment. Furthermore, brain cortex permeability and tight junction proteins were changed by IP MTX. miR-155 revealed its protective role in the current study for the development of MTX-induced cognitive impairment. Significance: IP MTX can induce significant cognitive impairment, which is related to the disruption of BBB integrity. miR-155 plays a vital role in the regulation of MTX-induced cognitive impairment, mainly through the maintenance of BBB integrity.